A review of noninvasive ultrasound image processing methods in the analysis of carotid plaque morphology for the assessment of stroke risk - Kyriacou, Efthyvoulos C.; Pattichis, Constantinos S.; Pattichis, Marios S.; Loizou, Christos P.; Christodoulou, Christodoulos; Kakkos, Stavros K.; Nicolaides, Andrew N. (My University, 2010)
Noninvasive ultrasound imaging of carotid plaques allows for the development of plaque-image analysis methods associated with the risk of stroke. This paper presents several plaque-image analysis methods that have been developed over the past years. The paper begins with a review of clinical methods for visual classification that have led to standardized methods for image acquisition, describes methods for image segmentation and denoising, and provides an overview of the several texture-feature extraction and classification methods that have been applied. We provide a summary of emerging trends in 3-D imaging methods and plaque-motion analysis. Finally, we provide a discussion of the emerging trends and future directions in our concluding remarks.
Keywords: Assessment of stroke; Carotid; Despekle filtering; Plaque imaging; Segmentation; Texture analysis; Ultrasound